Mitigasi Resiko Akad Pembiayaan Mudharabah pada Perbankan Syariah - Rahayu, Eka Jati (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2013)
Islamic banking began to develop in 1970 with a contract mudharabah (profitand loss sharing) as a trademark. Mudharabah contract believed to be able topush productivity rill sector and provide a solution to the global economic crisisdue to eliminating elements of interest. But the more sharia banking practiceapplying transaction-based contract (Murabahah) in various transactions. This is largely grounded in sharia banking risks incurred when applying mudharabah contract. Although many of the risk to be obtained, but it does not meanmudharabah contract can not be developed. Islamic banking can do a good riskmitigation mudharabah contract back up properly applied. The result foundis risk mudharabah contract, namely: First, agency problems. Second, theproblems of security. Third, investors and the role’s management. Fourth, timediversification effect on equities. Fifth, asset management. Islamic banking canapply risk mitigation, namely: First, the setting of the availability of surety andfix assets as collateral. Second, insist on maximal ratio of operational costs tooperating income. Third, the principle of Profit and Loss on contract shariangcapital participation and sharing in contract assembly reveue funds.